Continuous selections via geodesics - Colombo, Giovanni; Goncharov, Vladimir V. (Topological Methods in Nonlinear Analysis, 2001)
Some continuous selection results for a class of nonconvex-valued mapsare obtained. One of them contains Michael's theorem, in the case of aHilbert codomain. Methods of nonsmooth analysisand $Γ$-convergence are used.